Selección de habitat y distribución territorial de un grupo de vacas en ambiente de dehesa - Miguel J.-M. de; Rodríguez M.A.; Gómez Sal A. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
From a sampling based on systematic routes, the territorial distribution of a herd of about 400 cows on a 3000 ha 'dehesa' is analysed. The animals' preference and aggregation degree as regards homogeneous territorial areas, detected according to vegetation, geomorphology and land use, are studied. The presence of cows was discovered in only 51 per cent of the sampled units and clear asymmetries were found between them (80 per cent for environments with large isolated trees and 18 per cent in shrubby and rockrose thickets areas). Animal dispersion is analysed in the different seasons and according to the influence of forage supply.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)